Differences in Clinical Profile and Outcomes of Low Iron Storage vs Defective Iron Utilization in Patients With Heart Failure: Results From the DEFINE-HF and BIOSTAT-CHF Studies - Grote Beverborg, Niels (JAMA Cardiol, 2019)
IMPORTANCE: Iron deficiency is present in half of patients with heart failure (HF) and is associated with increased morbidity and an impaired prognosis. Iron deficiency due to low iron storage (LIS) and defective iron utilization (DIU) are not entirely the same clinical problem, although they generally receive the same treatment. OBJECTIVE: To define and describe similarities and differences between LIS and DIU in patients with HF. DESIGN, SETTING, AND PARTICIPANTS: This analysis included data from 2 prospective observational studies: the Definition of Iron Deficiency in Chronic Heart Failure (DEFINE-HF) study, a single-center study conducted from 2013 to 2015 including 42 patients with a reduced left ventricular ejection fraction of 45% or less scheduled for coronary artery bypass graft surgery, and the A Systems Biology Study to Tailored Treatment in Chronic Heart Failure (BIOSTAT-CHF) study, a multinational study conducted from 2010 to 2014 including 2357 patients with worsening HF from 69 centers in 11 countries. The median (interquartile range) follow-up time was 1.8 (1.3-2.3) years. Data were analyzed from January 2018 to January 2019. MAIN OUTCOMES AND MEASURES: The DEFINE-HF cohort was set up to derive a definition for different etiologies of iron deficiency using bone marrow iron staining as the criterion standard. This definition was applied to the BIOSTAT-CHF cohort to assess its association with clinical profile, biomarkers, and the primary composite end point of all-cause mortality or HF hospitalizations. RESULTS: Among the 42 patients in the DEFINE-HF study, 10 (24%) were women, and the mean (SD) age was 68.0 (9.5) years. Low iron storage was defined as a bone marrow–validated combination of transferrin saturation less than 20% and a serum ferritin concentration of 128 ng/mL or less; DIU was defined as transferrin saturation less than 20% and a serum ferritin concentration greater than 128 ng/mL. These criteria were applied to 2356 patients with worsening HF in the BIOSTAT-CHF study; 1074 (45.6%) were women, and the mean (SD) age was 68.9 (12.0) years. A total of 1453 patients with worsening HF (61.6%) had iron deficiency, of whom 960 (66.1%) had LIS and 493 (33.9%) had DIU. Low iron storage was characterized by a higher proportion of anemia and a poorer quality of life, while DIU was characterized by higher levels of various inflammatory markers. Both LIS and DIU were associated with an impaired 6-minute walking test. Low iron storage was independently associated with the composite end point of all-cause mortality or HF hospitalizations (hazard ratio, 1.47; 95% CI, 1.26-1.71; P < .001), while DIU was not (hazard ratio, 1.05; 95% CI, 0.87-1.26; P = .64). CONCLUSIONS AND RELEVANCE: In this study, both LIS and DIU were prevalent in patients with HF and had a distinct clinical profile. Only LIS was independently associated with increased rates of morality and HF hospitalizations, while DIU was not.